What would Wittgenstein say about social media?. (December 2017) - Brooker, Phillip; Dutton, William; Greiffenhagen, Christian
Much of the excitement in social media analytics revolves around, a) capturing large-scale collections of naturally-occurring talk, b) repurposing them as data, and, c) finding ways to speak sociologically about them. Researchers have raised concerns over the use of social media data in research (for example, boyd and Crawford, 2012; Housley et al, 2014; Tinati et al, 2014), exploring the ontological and epistemological grounding of the emerging field. We contribute to this debate by drawing on Wittgensteinian philosophy to elucidate hitherto neglected aspects; namely that it is not just social scientists who are in the business of analysing social media, but users themselves . We explore how mainstream social media analytics research (1) overinflates the importance of sociological theories, concepts and methodologies (which do not typically feature in the accounts of social media users), (2) downplays the extent to which social media platforms already exhibit order prior to any sociological accounting of them, and, (3) thereby produces findings which explain social scientific perspectives rather than the phenomena themselves. We reformulate the ontological and epistemological basis of social media analytics research from a Wittgensteinian perspective concerned with what it makes sense to say about social media, as members of society and as researchers studying those members. Such a project aims to explore social media users' language as a practice embedded within the context of social life and online communication. This reflects the everyday use of language as an evolving toolkit for undertaking social interaction, pointing towards an alternative conception of social media analytics.